Team Training for Success: An Interprofessional Curriculum for the Resuscitation of Emergency and Critical Patients - Ambrose Wong; Maureen Gang; Lisa Wing; Grace Ng; Demian Szyld; Heather Mahoney (Association of American Medical Colleges, 2014)
Abstract Introduction Team training initiatives, a form of interprofessional education, have been implemented in hospitals nationwide in response to patient safety reports citing teamwork and communication failures among the most frequent contributors to errors. In the emergency department and critical care units, efficient resuscitation of acute patients is contingent upon skilled resuscitation teams employing effective teamwork and communication skills to provide reliable and safe care. Policymakers and leaders in health care recognize that interprofessional collaboration in the workplace is required to achieve efficient, coordinated, and high quality healthcare. This team-training curriculum was established and implemented in order to address this specific need. Methods This educational module has been created and implemented to bring together an interprofessional team consisting of emergency medicine or internal medicine residents and nurses to work together as a cohesive unit during the resuscitation of critical patients. The materials presented and the simulation scenarios provided highlight and teach role identification as well as effective communication and teamwork. Results Over seven sessions from July to September 2012, a total of 76 nurses and residents participated in the course in our department. We showed a significant improvement in teamwork attitudes as measured by the Agency for Healthcare Research & Quality's previously validated TeamSTEPPS™ Teamwork Attitudes Questionnaire. Discussion Due to the overwhelmingly positive response from the course participants, several other departments within our institution have started to create and implement a similar simulation-based course for team training in their departments as well.